Randomised prospective study compares efficacy of five different stomach tubes for rumen fluid sampling in dairy cows. (10th January 2015) - Steiner, S.; Neidl, A.; Linhart, N.; Tichy, A.; Gasteiner, J.; Gallob, K.; Baumgartner, W.; Wittek, T.
Abstract : The objective of the study was to compare the performance of five types of stomach tubes for rumen fluid sampling. Rumen fluid was sampled in rumen fistulated cows assigned to a 5×5 Latin square study design. The pH values of samples taken by stomach tubes and via fistulas were measured; the results were compared with indwelling sensor measurements. The practicability of the stomach tubes for regular use was tested in the field. Rumen fluid samples were obtained rapidly. Volumes for transfaunation could be obtained. The pH‐values of samples taken with the four out of the five tubes (Dirksen, Geishauser, tube 4 and a simple water hose used with a gag) did not show significant differences to samples taken via rumen fistulas. Mean differences ranged between −0.02 and +0.09. Samples taken with tube 4 and the water hose showed also no significant differences to pH‐sensor measurements. This study demonstrates that stomach tubes are suitable for rumen fluid sampling. Tube 4 seems to be the best probe for work in the field. It was well tolerated by the animals, saliva contamination is negligible. We, therefore, conclude that the evaluation of rumen acid base status in the field is possible.